Eksperimen Sains Sederhana Menggunakan Permen Caca: Strategi Pembelajaran Aktif untuk Anak Usia Dini - Dina Aulia Sitindaon; Fanny Chintya Saragih; Happy Juwita Zai; Masniwati Halawa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to describe the process and impact of a simple science experiment using Caca candies as an active learning strategy for early childhood education. The research is based on the need for science learning that is concrete, exploratory, and engaging, in accordance with the developmental characteristics of young children. The STEAM approach (Science, Technology, Engineering, Arts, Mathematics) serves as an integrative framework to support cognitive, language, socio-emotional, and fine-motor development. This descriptive qualitative research was conducted at TK Baptis Menteng Medan involving children aged 56 years. Data were collected through direct observations, semi-structured interviews with teachers, and documentation in the form of photos and videos.The findings indicate that the simple rainbow experiment using Caca candies effectively enhances childrens scientific observation skills, language development, and social collaboration. Children showed high enthusiasm, were able to identify color changes, make simple predictions, and communicate their observations verbally and visually. STEAM integration was evident through activities such as observing color diffusion (Science), watching instructional videos (Technology), organizing procedural steps (Engineering), coloring and drawing (Arts), and grouping and counting candies (Mathematics). The three-day learning sequence provided meaningful and enjoyable learning experiences aligned with the principles of the Merdeka Curriculum. Therefore, the simple science experiment using Caca candies is an effective, low-cost, and practical active learning strategy for early childhood education.